2020
DOI: 10.1016/s2468-2667(20)30116-x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of food taxes and subsidies on population health and health costs: a modelling study

Abstract: Background One possible policy response to the burden of diet-related disease is food taxes and subsidies, but the net health gains of these approaches are uncertain because of substitution effects between foods. We estimated the health and cost impacts of various food taxes and subsidies in one high-income country, New Zealand. MethodsIn this modelling study, we compared the effects in New Zealand of a 20% fruit and vegetable subsidy, of saturated fat, sugar and salt taxes (each set at a level that increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
67
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(79 citation statements)
references
References 29 publications
1
67
0
Order By: Relevance
“…A two-pronged approach is required—empowering women with the tools to change the way they respond to the environment, and also changing their environment, where possible, to make healthier choices easier to make. The sugar tax, intended to create shifts in consumer behaviour, has reduced sugar consumption in the United Kingdom and Mexico [ 62 ], with higher effects for lower-income households. While food taxes and subsidies have not yet been implemented in Australia [ 63 ], it stresses the importance of giving women evidence-informed guidance they can trust, but also individual support to counteract obesogenic environments [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…A two-pronged approach is required—empowering women with the tools to change the way they respond to the environment, and also changing their environment, where possible, to make healthier choices easier to make. The sugar tax, intended to create shifts in consumer behaviour, has reduced sugar consumption in the United Kingdom and Mexico [ 62 ], with higher effects for lower-income households. While food taxes and subsidies have not yet been implemented in Australia [ 63 ], it stresses the importance of giving women evidence-informed guidance they can trust, but also individual support to counteract obesogenic environments [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…They found that the combined approach averted as many as 470,000 disability-adjusted life years, with cost-savings of AU$3.4 billion (~$2.3 billion) [52]. In a model examining the impact of a fruit and vegetable subsidy on the health-adjusted life years of New Zealand's population, 212 health-adjusted life years were gained through a 20% subsidy on fruits and vegetables [53]. These studies hint at the positive effect of redistributing agricultural subsidies to support the production of fruits and vegetables, in order to reduce cardiometabolic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The growth of civilisational ailments such as obesity or diabetes (WHO, 2020a(WHO, , 2020b and the increasing health-related costs (Blakely et al, 2020) are valid reasons to justify widespread dietary changes.…”
Section: Introductionmentioning
confidence: 99%